Pengaruh Financial Stability, External Pressure, dan Arogansi Terhadap Kecurangan Laporan Keuangan Pada Perusahaan Sektor Consumer Non-Cyclical - Fatimatuz Zahro' (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study aims to examine the effect of financial stability, external pressure, and arrogance on financial statement fraud in consumer non-cyclicals sector companies listed on the Indonesian Stock Exchange for the 2017-2021 period. The method used is purposive sampling with a total sampling with a total of population is 98 companies and total of sample is 170 research data. The analysis technique used is multiple linear regression analysis of panel data using Eviews 12. The results of this study indicate that financial stability has positive effect on financial statement fraud, external pressure has no effect on financial statement fraud, arrogance has has no effect on financial statement fraud.